2019
DOI: 10.1080/09168451.2019.1644149
|View full text |Cite
|
Sign up to set email alerts
|

Fecal metabolite of a gnotobiotic mouse transplanted with gut microbiota from a patient with Alzheimer’s disease

Abstract: Studies of Alzheimer’s disease are based on model mice that have been altered by transgenesis and other techniques to elicit pathogenesis. However, changes in the gut microbiota were recently suggested to diminish cognitive function in patients, as well as in model mice. Accordingly, we have created model mice of the human gut microbiota by transplanting germ-free C57BL/6N mice with fecal samples from a healthy volunteer and from an affected patient. These humanized mice were stably colonized and reproduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 55 publications
1
65
0
Order By: Relevance
“…In a germ-free AD mouse model, FMT with conventional microbiota or conventional AD microbiota caused an increase of pathology, with the latter showing a stronger effect (Harach et al, 2017). Another study with germ-free wild-type mice found a deterioration of cognitive function with lower fecal metabolites related to the nervous system, such as GABA, in aged, and not young, mice that received AD feces compared to healthy control feces (Fujii et al, 2019). Cui et al (2018) found that the chronic noise exposureassociated increased risk for AD in mice may be mediated by the gut microbiota, and that chronic noise causes agerelated neurochemical and inflammatory dysregulation.…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 99%
“…In a germ-free AD mouse model, FMT with conventional microbiota or conventional AD microbiota caused an increase of pathology, with the latter showing a stronger effect (Harach et al, 2017). Another study with germ-free wild-type mice found a deterioration of cognitive function with lower fecal metabolites related to the nervous system, such as GABA, in aged, and not young, mice that received AD feces compared to healthy control feces (Fujii et al, 2019). Cui et al (2018) found that the chronic noise exposureassociated increased risk for AD in mice may be mediated by the gut microbiota, and that chronic noise causes agerelated neurochemical and inflammatory dysregulation.…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 99%
“…MS patients received FMT showed improvement in disease progression [ 212 ] and MS symptoms [ 213 ]. Fecal microbiota from AD patients to GF mice affect mouse behaviors and less production of γ-aminobutyrate, taurine, and valine in vivo [ 214 ]. The 71-year-old PD patients had FMT from healthy young donors.…”
Section: Interaction Of Gut and Nervous System: Gut–brain Axismentioning
confidence: 99%
“…Thus, it was revealed that the gut microbiota of the mother mouse is involved in the behavior of the offspring mouse. In addition, the authors previously reported cognitive behavior decline in germ-free mice transplanted with the microbiota of AD patients (57) (Figure 2). In this article, these data were re-analyzed by linear regression analysis (Figure 3).…”
Section: Gut Microbiota and Behaviormentioning
confidence: 91%